2014
DOI: 10.1097/qai.0000000000000064
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Costs and Effects of Antiretroviral Therapy Task Shifting From Physicians to Other Health Professionals in Ethiopia

Abstract: Shifting the handling of both severe drug reactions and antiretroviral drug regimen changes from physicians to other clinical officers is not associated with a significant change in the 2-year treatment success rate or the costs of ART care. As an observational study, these results are tentative, and more research is needed in determining the optimal patterns of task shifting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…B., et al (2011) [46]UgandaComparison of a Pharmacy-only Refill Program (PRP) to Standard of Care for treatment for HIV/AIDS patientsOutputCost per person per year from societal and Ministry of Health perspective21% reduction in societal costs from Standard of Care ($665) to PRP ($520) and 17% reduction in MoH costs from Standard of Care ($610) to PRP ($496)No statistically significant difference in favorable immune response among patients in two groupsBemelmans, M., et al (2014) [48]South AfricaAdherence club for ARVs led by lay counselor and offered to all clinically stable patients who had been on ARVs for greater than 12 months; Club met every 2 months for essential medical tasks (e.g., weighing and health assessment) and distribution of ARVsOutputCost per patient per year46% reduction from mainstream model of care ($108) to ARV club model ($58)<1% mortality at 40 months, and 2.8% loss to follow up at 40 months in ARV clubFatti, G., et al (2015) [45]South AfricaIndirectly Supervised Pharmacist Assistant (ISPA) program compared to nurse-managed models for providing ARTsInput/processHuman resource costs and costs per item dispensed29% reduction in human resource costs from nurse-managed program ($1.89 per patient visit) compared to ISPA model ($1.35 per patient visit); 49% reduction in cost per item dispensed from nurse-managed program ($0.83) to ISPA model ($0.43)Cumulative attrition lower at ISPA sites (20.7% compared to 31.5%); proportion of patients achieving virological suppression higher at ISPA sites (89.6% compared to 85.9%)Foster, N. and D. McIntyre (2012) [47]South AfricaIndirectly Supervised Pharmacist Assistant (ISPA) program and nurse-managed models compared to full-time pharmacist for providing ARTsInput/processCost per patient visit43% reduction in cost from nurse-driven model ($10.16) to ISPA model ($5.74) and 12% reduction in cost from full-time pharmacist model ($6.55)Johns, B. and E. Baruwa (2015) [31]NigeriaComparison of hospital-based distribution of ART (by doctors) with clinic-based distribution of ART (by nurses and/or community pharmacists) for stable patients who had been on ART for at least 1 year, in two states aiming to decentralize health servicesOutputTotal cost per person per yearTotal costs increased in one state by 31% and decreased in one state by 32%; In both cases, the largest difference in costs between the hospital and clinic sites was staff cost/patient visitFew statistically significant differences found in service utilization indicators between patients going to clinic sites versus hospital sites; Patients in the state that achieved cost savings had 3.7× more visits per year than in hospitals ( p  < .01)Johns, B., et al (2014) [30]EthiopiaComparison of minimal, moderate, and maximal task shifting for ARV responsibilities away from physicians with hospital-based ARV distribution . Minimal = nonphysicians clinicians (NPC) monitor ART; Moderate = NPC initiate and ...…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…B., et al (2011) [46]UgandaComparison of a Pharmacy-only Refill Program (PRP) to Standard of Care for treatment for HIV/AIDS patientsOutputCost per person per year from societal and Ministry of Health perspective21% reduction in societal costs from Standard of Care ($665) to PRP ($520) and 17% reduction in MoH costs from Standard of Care ($610) to PRP ($496)No statistically significant difference in favorable immune response among patients in two groupsBemelmans, M., et al (2014) [48]South AfricaAdherence club for ARVs led by lay counselor and offered to all clinically stable patients who had been on ARVs for greater than 12 months; Club met every 2 months for essential medical tasks (e.g., weighing and health assessment) and distribution of ARVsOutputCost per patient per year46% reduction from mainstream model of care ($108) to ARV club model ($58)<1% mortality at 40 months, and 2.8% loss to follow up at 40 months in ARV clubFatti, G., et al (2015) [45]South AfricaIndirectly Supervised Pharmacist Assistant (ISPA) program compared to nurse-managed models for providing ARTsInput/processHuman resource costs and costs per item dispensed29% reduction in human resource costs from nurse-managed program ($1.89 per patient visit) compared to ISPA model ($1.35 per patient visit); 49% reduction in cost per item dispensed from nurse-managed program ($0.83) to ISPA model ($0.43)Cumulative attrition lower at ISPA sites (20.7% compared to 31.5%); proportion of patients achieving virological suppression higher at ISPA sites (89.6% compared to 85.9%)Foster, N. and D. McIntyre (2012) [47]South AfricaIndirectly Supervised Pharmacist Assistant (ISPA) program and nurse-managed models compared to full-time pharmacist for providing ARTsInput/processCost per patient visit43% reduction in cost from nurse-driven model ($10.16) to ISPA model ($5.74) and 12% reduction in cost from full-time pharmacist model ($6.55)Johns, B. and E. Baruwa (2015) [31]NigeriaComparison of hospital-based distribution of ART (by doctors) with clinic-based distribution of ART (by nurses and/or community pharmacists) for stable patients who had been on ART for at least 1 year, in two states aiming to decentralize health servicesOutputTotal cost per person per yearTotal costs increased in one state by 31% and decreased in one state by 32%; In both cases, the largest difference in costs between the hospital and clinic sites was staff cost/patient visitFew statistically significant differences found in service utilization indicators between patients going to clinic sites versus hospital sites; Patients in the state that achieved cost savings had 3.7× more visits per year than in hospitals ( p  < .01)Johns, B., et al (2014) [30]EthiopiaComparison of minimal, moderate, and maximal task shifting for ARV responsibilities away from physicians with hospital-based ARV distribution . Minimal = nonphysicians clinicians (NPC) monitor ART; Moderate = NPC initiate and ...…”
Section: Resultsmentioning
confidence: 96%
“…Of the 34 studies included in our review, 30 found evidence of a reduction in health costs either to the health system or the patient, and four had a mixed impact, an increase in costs, or no changes in costs [3033]. Almost all the studies focused on the effects of shifting clinical or public health tasks related to a specific disease or disease area, while one study focused on task shifting a HSS activity (mapping of village geographic coordinates) [34].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…15,16 This may signal that NPCs' deployment has finally gained full acceptance by local health sector leaders. The combined effect of the physician and nursing brain drain to urban, for-profit, and international settings and the boost in NPC training is a quiet but compelling transformation in the composition of sub-Saharan Africa's health workforce.…”
mentioning
confidence: 99%
“…Both UPF and TS have been proposed, for interventions ranging from rotavirus vaccination (Verguet et al 2013), to dental services (Jadidfard et al 2012) to emergency obstetric care (Kruk et al 2007;Scott and Campbell 2011;Bucagu et al 2012;Ejembi et al 2013;Sitrin et al 2013). In Ethiopia itself, task shifting is used to extend the treatment options for HIV patients (Johns et al 2014) and to provide comprehensive emergency obstetric care (Gessessew et al 2011). The Ministry of Health of Ethiopia has also set for itself a goal of training 800 emergency surgical officers by the end of 2015 (Ethiopia MoHo 2015).…”
Section: Discussionmentioning
confidence: 99%